Characterization of muscle phantom used in calibration of physiotherapy ultrasound: Measurement of acoustic parameters of phantom (2020) - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2021)
Physiotherapy ultrasound is one of the most used electrophysical agents in the clinic for its widely therapeutic effects. To guarantee safe and effective treatment, physiotherapy devices must be capable of applying correct ultrasound radiation to the body (or part of the body) under the procedure. The effectiveness of the therapy depends on the ultrasound device's performance and calibration. For performance testing and calibration, tissue-mimicking phantoms are used. This study's objective is to characterize the acoustic parameters of muscle phantom used in the calibration of physiotherapy ultrasound, by following per under the metrology principles. Muscle phantom was prepared. Then, the phantom's sound speed, attenuation coefficient was measured with the pulse-echo method, density, and acoustic impedance calculations were performed. A detailed uncertainty study in measurements was also presented in the paper. The acoustic parameters of muscle phantom were measured as given; the speed of sound 1549.8 ± 3.89 m/s (expanded uncertainty, U=6.7), attenuation coefficient 1.14 ± 0.8 dB/cm MHz (expanded uncertainty, U=0.55). Its acoustic impedance was calculated as 1.632 MRayl; it's density as 1053.5 kg/ m³. Muscle phantom's acoustic properties were found similar to the muscle tissue. It can be used in testing the physiotherapy ultrasound device's performance and calibration as it is cheap, easy to make, and © 2021 IEEE.
Keywords: Calibration; Characterization; Muscle phantom; Physiotherapy ultrasound